Specific probe for Hg2+ to delineate even H+ in pure aqueous buffer/Hct116 colon cancer cells: Hg(II)-eta(2)-arene pi-interaction and a TBET-based fluorescence response - Reddy, Upendar G.; Ramu, Vadde; Roy, Sovan; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new molecular probe that demonstrates a distinct TBET process, induced by the Hg(II)-eta(2)-arene pi-interaction, in pure aqueous medium with a large pseudo-Stokes shift of 200 nm.